Penetapan Margin dan Nisbah Bagi Hasil Pada Pembiayaan Mudharabah di Bank Syariah Indonesia - Shery Sutra Lena; Muhammad Syarofi (FAKULTAS EKONOMI DAN BISNIS ISLAMMM, 2022)
Sharia Bank is one of the financial institutions that provide services with sharia principles. In this case, Islamic banks refer to a system of banking activities that are consistent with sharia principles. Shari'a principles emphasize more on moral and ethical values ​​in all transactions carried out. Sharia prohibits the payment or receipt of interest charges or usury. There are various kinds of products offered by Islamic banking such as savings, financing, to various other service products. To understand this, through this research, the products offered by Islamic banks to avoid usury are formulated, namely Mudharabah products with a profit-sharing system. To implement the profit-sharing system, Islamic banks use two methods in determining the margin and ratio, namely profit-loss sharing and revenue-sharing methods. Keywords: Islamic Bank, Mudharabah Agreement, Margin and Ratio, Profit loss sharing, Revenue sharing.